CURRICULUM ANALYSIS OF THE TEACHER EDUCATION STUDY PROGRAM AT MADRASAH IBTIDAIYAH IAIN PALANGKA RAYA - Setria Utama Rizal; Sapuadi Sapuadi; Sutrisno Sutrisno (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractIncomplete curriculum documents for the Madrsasah Ibtidaiyah Teacher Education Study Program such as curriculum structure, study materials, and formulation of course learning outcomes. It is necessary that further curriculum redesign must refer to the latest regulations and be oriented towards the future. The curriculum preparation needs to involve stakeholders from the Education office, the Ministry of Religion, both at the city / provincial level. This research aims to analyze the preparation of the curriculum for the PGMI IAIN Palangka Raya Study Program referring to the Guidebook for Higher Education Curriculum Compilation. This research method uses descriptive-qualitative, while the data collection techniques uses interviews, observation, and documentation with the subjects of PGMI study program secretary, 4 homebase lecturers, and 10 PGMI students. The research results on the 2017 PGMI curriculum document are still lack of study material matrix according to the CPL, most of the courses have a weight of 2 credits, the courses on each semester are enough only 7 or 8 courses, the Semester Learning Plan (RPS) must be in accordance with the KPT book.Keywords: Analysis, Curriculum, PGMI